Effectiveness of Group Stress Reduction on Mental Health, Mothers' Quality of Life, and Behavioral Problems in Children with Attention Deficit Hyperactivity Disorder - Arash Mani; Leila Khabir; Samaneh Mousavinasab; Ahamad Ghanizadeh (Shiraz University of Medical Sciences, 2020)
Background: Children with attention deficit hyperactivity disorder (ADHD) run a high risk of behavioral problems. Their parents are also at risk of mental health and reduced quality of life. The present study aimed to investigate the effect of group mindfulness-based stress reduction on the parents of ADHD children and their mental health, quality of life, and behavioral problems. Methods: We conducted this single-blind randomized controlled clinical trial on 76 mothers with ADHD children aged 8-16 years referred to the clinics affiliated to Shiraz University of Medical Sciences. We randomly divided the patients into intervention and control groups. Group therapy included eight 45-minute sessions in two months and a three-month follow-up. The employed instruments were Strengths and Difficulties Questionnaire-parent form (SDQ-P), General Health Questionnaire-28 (GHQ-28), and Health related quality of life-short form-36 (HRQOL-SF-36). We analyzed all data by SPSS, and P values less than 0.05 were statistically significant. Results: After the intervention, the overall mean score for GHQ-28 (P<0.01) and dimensions of HRQOL-SF-36 (P<0.01), physical (P<0.001), and mental health significantly increased (P<0.01) and SDQ-P decreased (P<0.01) in the intervention group compared to the control group. Conclusion: Group mindfulness-based stress reduction was effective on mental health and quality of life in the parents of children with ADHD and could decrease child behavioral problems.